Antibiotic resistance in Campylobacter jejuni and Campylobacter coli: significant contribution of an RND type efflux pump in erythromycin resistance - Oncel, Beyza; Hasdemir, Ufuk; Aksu, Burak; Pournaras, Spyros (Taylor & Francis Ltd, 2024)
In this study, we aimed to determine the antibiotic resistance status of Campylobacter spp. isolated from human infections in our region, including the role of mechanisms involved in erythromycin resistance. Standard methods were used for the isolation, identification and antibiotic susceptibility testing of Campylobacter spp. isolates. Erythromycin-resistant mutants were selected from erythromycin-susceptible clinical isolates, and the erythromycin resistance mechanisms were investigated phenotypically by determining the erythromycin MICs of isolates in the presence and absence of the resistance nodulation cell division (RND) type efflux pump inhibitor, phenylalanine-arginine beta-naphthylamide dihydrochloride (PA beta N), and genotypically by determining ribosomal and cmeABC alterations using PCR and DNA sequence analysis. Campylobacter spp., including 184 C. jejuni and 20 C. coli in a two-year period, were the most frequently isolated gastrointestinal bacterial pathogens in our region. However, in both C. jejuni and C. coli, resistance to tetracycline and ciprofloxacin were found to be high, erythromycin resistance was especially high (20%) in C. coli. With a ribosomal alteration, A2075G, which was found to be associated with high-level erythromycin resistance in clinical isolates, PA beta N significantly reduced the erythromycin MICs in both clinical isolates and mutants. An important finding of this study, while considering cmeABC operon, is the explanation of why erythromycin resistance is more common among C. coli than C. jejuni, bearing in mind the specific deletions and alterations in the intergenic region of the operon in all erythromycin-resistant C. coli isolates. Ultimately, these findings revealed the significant role of RND-type efflux activity in increased erythromycin MICs of the isolates.
Keywords: Antibiotic resistance; Campylobacter; cmeABC operon; efflux; erythromycin; PA beta N